Complete mitochondrial genome of the green odorous frog Odorrana margaretae (Anura: Ranidae). (June 2015) - Chen, Zhuo; Zhang, Jie; Zhai, Xiaofei; Zhu, Yanjun; Chen, Xiaohong
Abstract The complete mitochondrial genome (mitogenome) of the green odorous frog Odorrana margaretae (Anura: Ranidae) has been studied. The 17, 903 bp circular genome contains the typical complement of 13 protein-coding genes, 2 ribosomal RNAs, 22 transfer RNAs, and a control region. The AT content of the overall base compositon of H-strand is 56% and the length of control region is 2501 bp with 63.8% AT content. The arrangement of the protein-coding and ribosomal RNA genes was the same as that found in other anurans. The cluster of rearranged LTPF tRNA genes and the translocation of tRNAHis gene into the D-loop region are observed.